THE INFLUENCE OF PERSONAL FACTORS, INSTITUTIONAL SUPPORT, AND MOTIVATION ON STUDENTS’ READINESS TO ENTER THE RENEWABLE ENERGY SECTOR - Saimara A.M. Sebayang; Maya Macia Sari; Annisa Ilmi Faried; Nor Harlinda Binti Harun; Nisa Ulzannah (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the determinants of student readiness to enter the renewable energy sector, emphasizing the influence of personal factors, institutional support, and motivation, as well as evaluating differences in readiness between students at Politeknik Tuanku Syed Sirajuddin (PTSS), Malaysia, and Universitas Pembangunan Panca Budi (UNPAB), Indonesia. The research problem focuses on the extent to which these three factors influence student readiness and the role of institutional differences in shaping work readiness. This study uses a descriptive and explanatory quantitative approach, with 60 final-year students as samples, selected through purposive sampling (30 students from each institution). Data were collected using a Likert scale questionnaire and analyzed through multiple linear regression, t- test, F-test, and coefficient of determination. The results show that personal factors (β = 0.207, t = 2.009, p = 0.041), institutional support (β = 0.254, t = 2.052, p = 0.045), and motivation (β = 0.291, t = 2.073, p = 0.043) significantly affect student readiness, with R² = 0.250. The difference test revealed that motivation (p = 0.025) and student readiness (p = 0.044) were higher at PTSS than at UNPAB, while personal factors did not show significant differences (p = 0.729). These findings emphasize the importance of strengthening motivation and institutional support in improving student readiness to enter the workforce in the renewable energy sector.